Analysis Of Profitability Performance In Sharia Commercial Banks Period 2018 – 2022 - Olfat Rayfadil Nabawi; Marlina Marlina (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2023)
Abstract This study aims to analyze the factors influencing the profitability ratio of Islamic Commercial Banks during the period 2018-2022. The research method used in this study is panel regression analysis. The data utilized is panel data comprising several Islamic commercial banks registered with the Indonesian Financial Services Authority (OJK) over the five-year period. The dependent variable in this research is the profitability ratio, measured by return on assets (ROA). The independent variables include factors believed to affect profitability, such as liquidity, capital adequacy, and non-performing financing. The analysis results indicate that liquidity, capital adequacy, and non-performing financing do not have a significant impact on profitability. This study contributes to the understanding of the factors influencing the profitability of Islamic commercial banks in Indonesia. The findings can be utilized by bank management and regulators to improve financial performance and identify crucial factors for optimizing the profitability of Islamic commercial banks. Keywords: profitability, sharia commercial banks, liquidity, capital, non-performing financing.